2002
DOI: 10.1002/smj.277
|View full text |Cite
|
Sign up to set email alerts
|

Perceived fairness, decision control, and commitment in international joint venture management teams

Abstract: Previous research examining the effectiveness of international joint ventures (IJVs) has focused on differences in the backgrounds and bargaining power of IJV parent firms, while little attention has been given to the IJV itself. This study takes a different perspective by examining the relationship between IJV parent firms and the IJV. Specifically, we examine how IJV and parent involvement in strategic decision-making influences the IJV management team's commitment to the IJV and to the parent firms. We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 80 publications
4
117
0
2
Order By: Relevance
“…Fourth, the concern for generalizabiltiy is also brought about by the relatively small sample size of this study although the sample represents possibly 40.8% of all existing small hemodialysis centers that have formed alliances with others in Taiwan. The 75 valid responses obtained in this study is comparable with sample sizes of 51 36 and 68 9 reported in previous cooperative alliance studies that have looked at IJVs. Finally, further research could be conducted to see if the measurement is applicable to other industry settings.…”
Section: Limitations and Future Directionssupporting
confidence: 83%
“…Fourth, the concern for generalizabiltiy is also brought about by the relatively small sample size of this study although the sample represents possibly 40.8% of all existing small hemodialysis centers that have formed alliances with others in Taiwan. The 75 valid responses obtained in this study is comparable with sample sizes of 51 36 and 68 9 reported in previous cooperative alliance studies that have looked at IJVs. Finally, further research could be conducted to see if the measurement is applicable to other industry settings.…”
Section: Limitations and Future Directionssupporting
confidence: 83%
“…… Fair procedures thus help protect and strengthen individuals' identification with the group or organization." (Johnson, Korsgaard, Sapienza, 2002, p. 1145. Further, "Organizational commitment and trust create social capital, which in turn fosters and supports knowledge creation and organizational learning" (Nahapiet andGhoshal, 1998, in ibid, p. 1142).…”
Section: Fairnessmentioning
confidence: 99%
“…Investigations have shown that a party may perceive low procedural justice as tending to deliver low commitment to the joint venture (Johnson, Korsgaard & Sapienza, 2002). Similarly, Luo (2005) found that alliance profitability was higher when both parties perceived higher rather than lower procedural justice.…”
Section: Proposition 2: In the Context Of Sci There Is A Positive Rementioning
confidence: 99%